Tributyltin in Crustacean Tissues: Analytical Performance and Validation of Method - Cristale, Joyce [UNESP] (2012)
The hermit crab Clibanarius vittatus is a typical organism from intertidal regions being considered as a good bioindicator of tributyltin presence at these environments. Thus this study presents the analytical performance and validation method for TBT quantification in tissues of C. vittatus by gas chromatography with pulsed flame photometric detector (GC-PFPD) after extraction with an apolar solvent (toluene) and Grignard derivatization. The limits of detection of the method (LOD) were 2.0 and 2.8 ng g(-1) for TBT and DBT (dibutyltin), respectively, and its limits of quantification (LOQ) were 6.6 and 8.9 ng g(-1) for TBT and DBT, respectively. The method was applied to samples from Santos Estuary, São Paulo State, Brazil. TBT and DBT concentrations ranged from 26.7 to 175.0 ng g(-1) and from 46.2 to 156.0 ng g(-1), respectively. These concentrations are worrisome since toxic effects (such as endocrine disruption) have been reported for other organisms even under lower levels of registred at this study.